1992
DOI: 10.1192/bjp.160.2.217
|View full text |Cite
|
Sign up to set email alerts
|

Sertraline in the Prevention of Depression

Abstract: A group of 480 patients, aged 19-78 with an HRSD score of at least 17 and who met DSM-III criteria for major depressive disorder were studied. Patients were given placebo for a one-week single-blind run-in period, after which sertraline was administered for eight weeks. This was followed by 44 weeks in which patients received sertraline or placebo on a double-blind, randomised basis. Patients were assessed periodically using the 17-item HRSD and the Clinical Global Impression scales. During the entire double-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
94
0
1

Year Published

1995
1995
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(100 citation statements)
references
References 8 publications
5
94
0
1
Order By: Relevance
“…Twelve trials (13 placebo comparisons) were shorter than 1 year for the randomized followup (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)29,40). These trials provide consistent evidence in favor of active drug over placebo, with the majority representing the efficacy of relapse prevention.…”
Section: Placebo-controlled Trialsmentioning
confidence: 84%
See 1 more Smart Citation
“…Twelve trials (13 placebo comparisons) were shorter than 1 year for the randomized followup (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)29,40). These trials provide consistent evidence in favor of active drug over placebo, with the majority representing the efficacy of relapse prevention.…”
Section: Placebo-controlled Trialsmentioning
confidence: 84%
“…Trials shorter than 1 year-Twelve trials were included in our relative risk meta-analysis of trials lasting less than 1 year after randomization ( Figure 1): one on bupropion (18), three on citalopram (19,27,40), one on escitalopram (20), three on fluoxetine (21,22,29), and one each on mirtazapine (23), nefazodone (24), sertraline (25), and venlafaxine (26). The pooled relative risk of relapse was 0.54 (95% CI 0.46 to 0.62) and the NNT to prevent one additional relapse over a mean time of 8 months was 5 (95% CI: 4-6).…”
Section: Meta-analysismentioning
confidence: 99%
“…This is not an insignificant problem since recurrence rates vary from 15 to 40% in long-term clinical trials, a proportion mirrored in clinical practice (Coppen et al, 1978;Prien et al, 1973Prien et al, , 1984Montgomery et al, 1988;Rouillon et al, 1989;Frank et al, 1990;Doogan and Caillard, 1992;Kupfer et al, 1992;Montgomery and Dunbar, 1993). Patients who relapse in spite of continuing their treatment may be demoralized and refuse further treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Placebo-controlled continuation studies with adults have shown that continued treatment with an anti-depressant for 6-9 months after acute treatment reduces relapse rates compared with placebo (14)(15)(16). In a small pilot study conducted as part of a large acute efficacy trial of fluoxetine in children and adolescents, continued fluoxetine reduced relapse rates compared with placebo (34% and 60%, respectively) and lengthened the time to relapse (17).…”
mentioning
confidence: 99%